Comprehensive Management of Polycystic Ovary Syndrome: The Role of Metformin in Addressing Metabolic and Endocrine Dysregulation - Martyna Kaźmierczak; Jakub Parys; Agnieszka Mikosińska; Patrycja Kałuziak; Marta Jajaczak; Maciej Mossakowski; Aleksandra Witek; Mateusz Litwin; Stanisław Jesionek (Journal of Education, Health and Sport)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine and metabolic disorder that affects women of reproductive age, characterized by hormonal imbalances, insulin resistance, and a range of clinical manifestations, including infertility and metabolic disturbances. Effective management of PCOS remains a challenge due to its multifaceted nature, necessitating a comprehensive understanding of therapeutic options.